Listeria monocytogenes brain abscess in a patient with multiple myeloma - Al-Khatti, Adil A; Al-Tawfiq, Jaffar A (The Journal of Infection in Developing Countries, 2010)
Listeria monocytogenes is an uncommon cause of illness in the general population. Meningoencephalitis is the most common central nervous system (CNS) manifestation of listeriosis. However, brain abscess represents 1-10% of all CNS listeriosis. To our knowledge, L. monocytogenes brain abscess in multiple myeloma patients has not been previously reported. Thus we report a 58-year-old male patient with multiple myeloma who developed a brain abscess due to L. monocytogenes. Due to a history of penicillin allergy, he was treated with intravenous trimethoprim/sulfamoxazole (TMP-SMX) for a total of 12 weeks, and gentamicin for the first two weeks, followed by oral therapy of TMP-SMX for a total of nine months. He is alive six and a half years after the diagnosis of myeloma with occasional brief seizures despite being on two anticonvulsants.